Financial liberalisation, crisis, and restructuring: A comparative study of bank performance and bank governance in South East Asia - Williams, Jonathan; Nguyen, Nghia (Journal of Banking & Finance, 2005)
This paper examines the impact of changes in bank governance on bank performance for a sample of commercial banks operating in SE Asia between 1990 and 2003. We identify bank governance in terms of bank ownership and measure bank performance as rank order alternative profit efficiency, technical change, and productivity. The period was characterised by financial deregulation, the Asian crisis and bank restructuring programmes. To resolve financial distress, SE Asian authorities implemented inter alia bank privatisation programmes and widened access for foreign ownership. Our results tend to support bank privatisation and the repeal of state ownership on economic grounds. We suggest the potential benefits of foreign ownership may take longer to be realised. For domestic private-owned banks, the challenge is improving bank efficiency.